Fasakh Procedure in A Coma : Study of Islamic Family Enakmen in Seremban, Negeri Sembilan - Hana, Nur Farah; Lubis, Azwani (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
Abstract This study discusses the process of prosecution of a woman who was in a coma under the Enakmen of the Islamic Family Act under Section 53 and her success in the Syariah Court. The author finds that this type of research uses qualitative research with a normative jurisprudential approach based on Malaysian legislation and Islamic law. According to the provisions of the Islamic family law of each country in Malaysia, fasakh is one of the spouse's rights regulated in substantive law. This right has been clearly mentioned, and almost all the grounds given involve a husband's fault that can lead to neglect, persecution, and violence against his wife. No wonder the fasakh is the last choice that a wife who can no longer live with her husband has to make. This is because other types of divorce such as talaq, khulu ', and ta'liq can only be done with the consent of the husband. Since the judge has the authority to dissolve a marriage without the consent of the husband, the wife must present strong evidence to convince the Speaker that the grounds for the dissolution of the marriage are correct and in accordance with the will of the sharia. At the same time, the husband will also have enough time to defend himself from the accusations of the wife. The author also notes that the decision to decide on the endorsement of the prosecution of a woman who is in a coma has the authority of a Syariah judge in court. [Studi ini membahaskan tentang proses tuntutan fasakh seorang wanita yang koma menurut Enakmen Undang-Undang Keluarga Islam menurut Seksyen 53 dan keberhasilannya di Mahkamah Syariah. Penulis menemukan jenis penelitian ini menggunakan penelitian kualitatif dengan pendekatan yuridis normatif berdasarkan perundang-undangan Malaysia dan hukum Islam. Menurut peruntukan undang-undang keluarga Islam masing-masing negeri di Malaysia, fasakh adalah salah satu hak suami istri yang diatur dalam undang-undang substantif. Hak ini telah disebutkan dengan jelas, dan hampir semua alasan diberikan adalah melibatkan kesalahan suami yang dapat menyebabkan pengabaian, penganiayaan, dan kekerasan terhadap istri. Tidak mengherankan bahwa fasakh adalah pilihan terakhir yang harus diambil oleh istri yang tidak lagi dapat menjalani kehidupan bersama suaminya. Ini karena jenis perceraian lainnya seperti talaq, khulu’ dan ta'liq hanya dapat dilakukan dengan persetujuan suami. Oleh karena hakim memiliki wewenang untuk membubarkan perkawinan tanpa lafaz dan kebenaran suami, pihak istri harus mengemukakan bukti yang kuat untuk meyakinkan Hakim Bicara bahwa alasan untuk sabitan fasakh adalah tepat dan sesuai dengan kehendak syarak. Pada saat yang sama, suami juga akan memiliki waktu yang cukup untuk membela diri dari tuduhan istri. Penulis juga mencatatkan bahwa keputusan untuk menentukan kelulusan tuntutan fasakh bagi wanita yang sedang koma ini mendapat kekuatan hakim syarie di pengadilan.]